The Effects of a Combined Output and Input-Oriented Approach in Teaching Reported Speech - Mystkowska-Wiertelak, Anna (Research in Language, 2011)
The author of the present study investigates the effects of output and input-oriented treatment on the acquisition of English reported speech, a complex phenomenon posing considerable difficulty even to more advanced learners of the language. The study focuses on two research questions: Will there be any differences in how learners exposed to reception-oriented, production-oriented and a combined type instructional treatments interpret and produce sentences containing reported speech? Is the effect durable, as measured on immediate and delayed post-tests? The participants of the study are 74 first year students of the English philology who were divided into four groups: 3 treatment groups and a control one. The study results do not mirror those reported in the vast majority of relevant literature and points that although input manipulation appears to have more beneficial effect on the development of the interlanguage than the analysis of output, a combination of the two approaches turns out to be the most beneficial and economical.